Electronic administration as a mechanism to improve the performance of the public service in Algeria - Benkhedda, Aissa; Boumezber, Badis (Journal of Human Sciences, 2023)
The shift towards electronic administration has become a global trend that encourages the adoption of electronic services systems , because of their role in improving performance, speed of delivery and effectiveness of implementation, Therefore the Algerian authorities have implemented the electronic public service in various public facilities in order to meet the needs of citizens and keep pace with technological and scientific progress. Accordingly, this study aims to research the various aspects of electronic administration and its most important applications in Algeria, highlighting its advantages and identifying the most important obstacles and difficulties that limit its effectiveness in providing public services to the public in the best way.